Genetic alteration of the c-myc protooncogene (MYC) in human primary breast carcinomas. - Escot, C (1986)
We have studied the genomic organization of the c-myc locus (MYC) from 121 human primary breast carcinomas. Two types of alterations were observed: (i) the c-myc protooncogene appeared to be amplified 2- to 15-fold in 38 (32%) of the carcinoma DNAs and (ii) a non-germ-line c-myc-related fragment of variable size was detected in 5 primary breast carcinoma DNAs. With three exceptions, all the tumors containing a genetic alteration of the c-myc locus were invasive ductal carcinomas. A significant correlation (P less than 0.02) was observed between patients more than 50 years old and the presence of a genetically altered c-myc. Enhanced levels of c-myc RNA were observed in 10 of 14 breast carcinomas examined. The c-myc gene was genetically altered in 6 of these 10 tumors. The frequency with which the c-myc gene is altered and its correlation with age suggest that it may play a role in the development of breast carcinomas.